2015
DOI: 10.21769/bioprotoc.1374
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Protein Stability by the Cycloheximide Chase Assay

Abstract: Comparison of protein stability in eukaryotic cells has been achieved by cycloheximide, which is an inhibitor of protein biosynthesis due to its prevention in translational elongation. It is broadly used in cell biology in terms of determining the half-life of a given protein and has gained much popularity in cancer research. Here we present a full cycloheximide chase assay in our laboratory using a lung adenocarcinoma cell line, CL1-5, as a model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 2 publications
0
66
0
Order By: Relevance
“…31 Proteasomal blockade with either epoximicin or MG-132 led to a significant increase in the intracellular halflife of BMP2 following epoximicin treatment (Figure 2A; **P ≤ 0.01 at 30-and 60-min posttreatment with epoximicin and *P ≤ 0.05 at 30 and 60 minutes post-MG-132). 293T cells were transfected with a plasmid vector, expressing BMP2 and treated with cycloheximide (Chx) in presence or absence of proteasomal inhibitors.…”
Section: Half-life Through Posttranslational Mechanismsmentioning
confidence: 91%
See 1 more Smart Citation
“…31 Proteasomal blockade with either epoximicin or MG-132 led to a significant increase in the intracellular halflife of BMP2 following epoximicin treatment (Figure 2A; **P ≤ 0.01 at 30-and 60-min posttreatment with epoximicin and *P ≤ 0.05 at 30 and 60 minutes post-MG-132). 293T cells were transfected with a plasmid vector, expressing BMP2 and treated with cycloheximide (Chx) in presence or absence of proteasomal inhibitors.…”
Section: Half-life Through Posttranslational Mechanismsmentioning
confidence: 91%
“…Cycloheximide blocks de novo synthesis of proteins, allowing measurement of their steady-state turnover. 31 Proteasomal blockade with either epoximicin or MG-132 led to a significant increase in the intracellular halflife of BMP2 following epoximicin treatment (Figure 2A; **P ≤ 0.01 at 30-and 60-min posttreatment with epoximicin and *P ≤ 0.05 at 30 and 60 minutes post-MG-132). Addition of epoximicin and MG-132 led to significant delay in BMP2 degradation, almost doubling BMP2 half-life (Figure 2A; 30min post-cycloheximide addition in comparison to >60 minutes following addition of epoximicin or MG-132, *P ≤ 0.05 to P ≤ 0.01).…”
Section: Half-life Through Posttranslational Mechanismsmentioning
confidence: 91%
“…The CHX chase experiment was performed as described previously (60). Cells were seeded on 35-mm culture dishes at a density of 6 ϫ 10 6 cells.…”
Section: Cellmentioning
confidence: 99%
“…PP2CA plants ( Kao et al, 2015). As shown in Figure 1(b), PP2CA proteins were more degraded with ABA treatment versus no treatment.…”
Section: Resultsmentioning
confidence: 89%
“…To determine whether the PP2CA is degraded via the ubiquitin‐26S proteasome pathway, we treated each reaction mixture with the proteasome inhibitor MG132 (Joo et al ., ) and found that MG132 inhibited the degradation of the PP2CA protein. Moreover, we investigated the stability of PP2CA in vivo in the absence of de novo protein synthesis through cycloheximide (CHX) chase assay using 35S:: PP2CA plants (Kao et al ., ). As shown in Figure (b), PP2CA proteins were more degraded with ABA treatment versus no treatment.…”
Section: Resultsmentioning
confidence: 99%